2020
DOI: 10.1021/acs.molpharmaceut.0c00390
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable Nanocomposite Microparticles with Enhanced Dissolution and Superior Aerosol Performance

Abstract: Previous studies have shown that combining colistin (Col), a cationic polypeptide antibiotic, with ivacaftor (Iva), a cystic fibrosis (CF) drug, could achieve synergistic antibacterial effects against Pseudomonas aeruginosa. The purpose of this study was to develop dry powder inhaler formulations for co-delivery of Col and Iva, aiming to treat CF and lung infection simultaneously. In order to improve solubility and dissolution for the water-insoluble Iva, Iva was encapsulated into bovine serum albumin (BSA) na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“… a Average value ± standard deviation of three measurements. b Undetectable by HPLC where the limit of detection was ∼1 μg/mL. c Could not be measured due to crystallization. d Unable to pellet down amorphous drug-rich nano species. e Could not be determined. f Measured from flux studies; a detailed description can be found in ref . …”
Section: Resultsmentioning
confidence: 99%
“… a Average value ± standard deviation of three measurements. b Undetectable by HPLC where the limit of detection was ∼1 μg/mL. c Could not be measured due to crystallization. d Unable to pellet down amorphous drug-rich nano species. e Could not be determined. f Measured from flux studies; a detailed description can be found in ref . …”
Section: Resultsmentioning
confidence: 99%
“…This was also reflected in the higher FPF values. Solute concentration also contributed to this effect, as the lower the solute concentration was, the more porous and thus less dense the particles became, improving airflow and facilitating powder aerosolization [ 26 , 27 ]. In contrast, solute concentration did not appear to have a major role, despite the statistical analysis, which indicated that it had a negative impact on powder dispersibility.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many successful examples of MDP-loaded DPI formulations have been reported in the literature 314 , 337 , 338 , 339 . Among them, the development of DPI formulations for the co-delivery of MDP and other drugs has gradually become a research hotspot, not only because of their potential to afford enhanced therapeutic effects but also because of their potential to increase the aerosol performance of formulations.…”
Section: Mdps-based Formulations and Their Applicationsmentioning
confidence: 99%
“…In order to simultaneously treat cystic fibrosis and its complications, such as multidrug-resistant Gram-negative lung infections, Zhou's group 339 recently reported a novel, inhalable nanocomposite microparticle formulation for co-delivery of colistin and ivacaftor. The authors demonstrated that colistin could work not only as a synergistic antimicrobial agent, but also as a unique matrix material for reducing the use of excipients for high-dose medications, improving the dissolution rate of ivacaftor, and increasing the aerosol performance of formulations.…”
Section: Mdps-based Formulations and Their Applicationsmentioning
confidence: 99%